Consenting practices in interventional cardiology: an analysis from the European Association of Percutaneous Cardiovascular Interventions (EAPCI). (3rd October 2022) - Rajkumar, C A; Bello, O; McInerney, A; Tilsted, H H; Johnson, V; Fovino, L N; Fitzsimons, D; Al-Lamee, R; Byrne, R
Abstract: Background: Consenting practices in interventional cardiology vary across different procedures, operators, centres and nations. Purpose: In order to define best practice for obtaining informed patient consent, it is first necessary to understand how consenting practice differs. Methods: An online survey of 20 questions was sent to all members of the European Association of Percutaneous Cardiovascular Interventions, addressing consenting practices in elective and emergency scenarios. Results: We received 483 responses from 74 countries. The majority of respondents (77%) were European operators. Responses were received from consultant cardiologists (n=370), fellows in training (n=55), allied health professionals (n=36) and others (n=21). Across all respondents, in elective practice, 427 (88.4%) operators obtain written consent for every procedure, the remainder (9.5%) obtain verbal consent only. Consent is obtained by the consultant or fellow who directly performs the procedure in 56.9% cases. For coronary angiography, pre-emptive consent for possible additional procedures (pressure wire and PCI) is taken by operators in all cases (58.6%), some cases (30.6%) and never (11.0%). Prior to interventional therapies, written information detailing the risk of the procedure is provided in every case by 63.8% of operators, sometimes by 25.1% of operators, and is never provided by 11.0% of operators. In emergency settings, where patients are conscious and have capacity to consent, 274 (56.7%) of respondents obtain written consent, 155 (33.1%) obtain verbal consent only and 52 (10.8%) stated that a consent process was not required. Where consciousness and capacity are impaired, 218 (45.1%) always, 118 (24.4%) sometimes and 145 (30%) never document a written capacity and best interests' assessment. When asked to rate the overall quality of consenting practices in their own institution, 279 (57.8%) stated these were "excellent" or "above average", 165 (34.2%) were "average" and 39 operators described consenting practices in their institution as "below average" or "poor". Conclusions: Diversity in consenting practice spans elective and emergency procedures. These results suggest that there is substantial variation in the understanding of the rationale, legal requirement, and perceived best practices for consent. Further work should consider the merits of standardisation of consent processes across Europe. Funding Acknowledgement: Type of funding sources: None.